The Readability Level of Arabic Textbook “Silsilah Fī Ta’līm al-Lughah al-‘Arabiyyah” - Puti Zulharby; Ahmad Marzuq; Aziz Ritonga (LISANIA: Journal of Arabic Education and Literature, 2021)
The purpose of this study was to know the readability level of textbook "Silsilah Fī Ta’līm al-Lughah al-‘Arabiyyah: Al-Mustawā Ats-Tsāniy, Al-Qirā`ah", and factors  affecting readability level in terms of word class tendencies and linguistic findings. This study also analyzed the level of reading ability of first-semester Arabic students at Universitas Negeri Jakarta and the types of texts recommended for use or further development by other researchers. This research was carried out using descriptive qualitative methods, and data were collected from 83 students who enrolled in the Qirā`ah course. Readability analysis techniques using the Cloze Procedure Test. The research showed that the readability of textbooks was 46% at the frustration level and 29% at the moderate level. The tendency of the word class to make errors generally occur in 1) 27% of perfect verbs, 2) 24% of nouns, 3) 16% of imperfect verbs. Other factors are 1) Reader Factor: about 43% of students in the Arabic Language Education Department come  from general/vocational high schools, 35% from Islamic high school, and only 22% from Islamic boarding schools; 2) Reading Factor: the textbooks writers from native Arabic speakers generally rely on their experience and culture in presenting the text regardless of readers ability as foreign speakers. 3) Book Factor: this book lacks vocabulary and illustrations in the form of pictures, so that it was less helpful in independent understanding.